Protective effects of isorhamnetin against H2O2-induced oxidative damage in HaCaT cells and comprehensive analysis of key genes - Wen Hu; Jingzhan Zhang; Hongjuan Wang; Mengmeng Guan; Leheng Dai; Jun Li; Xiaojing Kang (Scientific Reports, 2023)
Abstract Isorhamnetin (ISO) is a methylated flavonol present in the leaves, flowers, and fruits of many plants with antitumour, anti-inflammatory, antioxidant, and anti-apoptotic properties. ISO has been suggested as the active substance in Vernonia anthelmintica (L.) to treat vitiligo. However, the mechanisms underlying its effects remain unclear. In this study, human keratinocytes (HaCaT cells) were pre-treated with or without ISO and then stimulated with hydrogen peroxide (H2O2) to generate oxidative damage. Pre-treatment with ISO increased HaCaT cell viability, reduced malondialdehyde content, and enhanced superoxide dismutase activity, resulting in a reduction in the loss of mitochondrial membrane potential, improved cell morphological damage, and apoptosis inhibition. Furthermore, we identified 51 significantly dysregulated differentially expressed genes (DEGs) of HaCaT cells treated with ISO using RNA-sequencing. Enrichment analysis using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases indicated that the protective effect of ISO could be related to its effects on the Wnt signalling pathway. Our study provides novel insights into key gene regulation in the progression of oxidative damage and the mechanisms of action of ISO.